The association between high ambient temperature and risk of hospitalization: a time-series study in eight ecological regions in Vietnam - Nu Quy Linh Tran; Hieu K T Ngo; Nguyen Thi Tuong Vy; Tran Ngoc Dang; Son Nghiem; Huu Quyen Nguyen; Dung Phung (IOP Publishing, 2023)
Viet Nam is among the countries most threatened by and vulnerable to climate change and extreme weather events. However, research on the temperature-morbidity relationship at the national scale has been scarce. This study aimed to assess the impact of high temperatures on the risk of hospital admissions for all causes and heat-sensitive diseases across eight ecological regions in Vietnam. The study utilized a longitudinal dataset that included hospitalization and meteorological data from eight provinces representing eight regions in Vietnam. A time series analysis was applied using the generalized linear and distributed lag models with a quasi-Poisson family to examine the temperature-hospitalization association in each province. A random-effects meta-analysis was used to calculate the pooled estimate of risk for the national scale. The country-level pooled effects (%, [95% CI]) indicated that a 1 °C increase above the threshold temperature (19 °C) increased the hospitalization risk for all causes and infectious diseases by 0.8% [0.4%-1.2%] and 2.4% [1.02%-1.03%], respectively at lag 0-3 d. The effects of heat on respiratory diseases and mental health disorders were not significant. At the regional level, the association varied across eight regions, of which the Northern parts tended to have a higher risk than the Southern. This is among very few national-scale studies assessing hospitalization risk associated with high temperatures across eight ecological regions of Vietnam. These findings would be useful for developing evidence-based heat-health action plans.